CRITICAL ANALYSIS OF THE CONSTRUCTIVIST PEDAGOGY - Berrocal Santos, Danny (2014)
The present document shows a brief critical analysis about the consequences that the adoption of the “constructivist pedagogy” implies as paradigmatic pedagogic model. This study begins for trying to give a definition of what is the constructivism to general level, then it traces the philosophical and epistemological foundations that give origin to the constructivism, as well as the pedagogic principles that sublie to the constructivist pedagogic current, then it finishes with a general balance sheet of the constructivist approach and with a critique of its foundations and the consequences and limitations that it involves in the educational level.